Trùng hợp điện hóa màng bảo vệ polypyrrol trực tiếp trên nền thép cacbon sử dụng salicylat làm ion đối - Dung, Nguyễn Tuấn (Vietnam Journal of Chemistry, 2014)
A homogeneous and adherent Polypyrrole (PPy) film can be electrodeposited on carbon steel surface in the aqueous media using salicylate counter-ion. Protective properties of obtained PPy films were studied in the solution NaCl 0.1 M by following the open circuit potential of system vs. immersion time. The influence of synthesis medium (pH value, monomer and electrolyte concentrations) and of applying current density was investigated. The protection time of the best PPy film electrosynthesized in acidic medium was about one week, whereas it was two weeks in the case of neutral synthesis medium. The result observed on the iron surface was about 3 months. It is very interesting to notice that the best protective PPy film can be obtained by a soft procedure, e.g. neutral medium and grand applying current density, which is well suitable for industry application.